The Level of Knowledge of the Tapaan Banyuates Sampang Community about Generic and Patent Medicine - Suprihatin (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2024)
Patent medicines are finished medicines with a trade name registered in the name of the manufacturer and sold in the original packaging from the factory that produces them. while generic drugs are drugs or the official International Non-proprietary Names (INN) specified in the Indonesian pharmacopoeia or other standard books or the efficacious substances in their contents. There are people who think that the quality of patented medicines with more expensive prices has good quality compared to generic medicines. So this research aims to determine public knowledge about patent medicines and generic medicines in Tapaan Banyuates Village, Sampang Regency. The type of research used is non-experimental research using a survey method with a quantitative analysis design and data collection methods in the form of questionnaires Each question item has a p-value <0.05. This means that the statements in the questionnaire can be used as a measuring tool for what will be measured, and a Cronbach alpha value of 0.8 means the questionnaire is reliable. Non-probability sampling data collection techniques, namely sampling based on certain considerations or criteria. The respondents used in this research were the Tapaan Banyuates Sampang village community aged > 18 years, both male and female, totaling 96 respondents. Data is presented in the form of tables, bar charts, and accompanied by discussion. Most of the respondents' level of knowledge about generic medicines was in the poor category with a percentage of 48%, while most of the respondents' level of knowledge about patented medicines was in the good category, namely with a percentage of 44%.